PENGEMBANGAN MEDIA PEMBELAJARAN PERMAINAN ETNO-MONOPOLI PADA MATERI BILANGAN CACAH FASE B SD - Handayani, Mika; Hainul Putra, Zetra; Fendrik, Muhammad (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2025)
This study aims to develop Ethno-Monopoly learning game media on whole number Phase B material for elementary school that is feasible for use in learning activities. The method used in this research is the research and development (R&D). Using the Plomp development model, into three phases (preliminary research, prototyping phase dan assessment phase). Data collection techniques include interviews, validation sheets, and questionnaires. The data analysis methods used are qualitative descriptive analysis and quantitative descriptive analysis. The results of the study are as follows: first, the product feasibility test by material experts, media experts, and language experts. The assessment by material experts yielded a percentage of 94.79% categorized as very valid, media experts’ assessment obtained 81.25% categorized as valid, and language experts’ assessment reached 92.86% categorized as very valid. Next, the evaluations from teachers and students showed that the teacher’s assessment was 95.83% categorized as very practical, while students’ assessment was 97.64% categorized as very practical. Therefore, the developed Ethno-Monopoly learning game media on whole number Phase B material for elementary school meets the criteria of validity and practicality.